2018
DOI: 10.1093/jee/tox373
|View full text |Cite
|
Sign up to set email alerts
|

Blends of Pheromones, With and Without Host Plant Volatiles, Can Attract Multiple Species of Cerambycid Beetles Simultaneously

Abstract: Pheromone components of cerambycid beetles are often conserved, with a given compound serving as a pheromone component for multiple related species, including species native to different continents. Consequently, a single synthesized compound may attract multiple species to a trap simultaneously. Furthermore, our previous research in east-central Illinois had demonstrated that pheromones of different species can be combined to attract an even greater diversity of species. Here, we describe the results of field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Field studies conducted in the eastern USA, where P. testaceus was introduced many decades ago (Swift and Ray 2010), have revealed inconsistent responses to the two compounds. For example, adults of P. testaceus were attracted in significant numbers to traps baited with 3-hydroxy-2-hexanone alone during bioassays that lacked a 2-methyl-1-butanol treatment, but only the latter compound was attractive when both compounds were presented as single compound treatments in other bioassays (Hanks and Millar 2013; Hanks et al 2018, 2019; Millar et al 2018). Other field trials conducted in the eastern USA, with traps baited with blends of cerambycid pheromones that included 2-methyl-1-butanol and 3-hydroxy-2-hexanone (Handley et al 2015; Hanks and Millar 2013), have also demonstrated significant attraction of P. testaceus to these blends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies conducted in the eastern USA, where P. testaceus was introduced many decades ago (Swift and Ray 2010), have revealed inconsistent responses to the two compounds. For example, adults of P. testaceus were attracted in significant numbers to traps baited with 3-hydroxy-2-hexanone alone during bioassays that lacked a 2-methyl-1-butanol treatment, but only the latter compound was attractive when both compounds were presented as single compound treatments in other bioassays (Hanks and Millar 2013; Hanks et al 2018, 2019; Millar et al 2018). Other field trials conducted in the eastern USA, with traps baited with blends of cerambycid pheromones that included 2-methyl-1-butanol and 3-hydroxy-2-hexanone (Handley et al 2015; Hanks and Millar 2013), have also demonstrated significant attraction of P. testaceus to these blends.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of ( R )- and ( S )-3-hydroxy-2-hexanone for comparison with the insect-produced compounds were available from previous work (Lacey et al 2007). Racemic 2-methyl-1-butanol and its ( S )-enantiomer, and 2,3-hexanedione were purchased from Aldrich Chemical Co. (Milwaukee, WI, USA), and ( R )-2-methyl-1-butanol was prepared by reduction of ( R )-2-methylbutanoic acid as described in Hanks et al (2018). 1-Hexanol (reagent grade 98%, CAS 111–27-3, Sigma-Aldrich, Hamburg, Germany) and racemic 2-methyl-1-pentanol (99.8%, CAS 105–30-6, Dr. Ehrenstorfer GmbH, Augsburg, Germany) were purchased to confirm the identities of trace compounds in extracts from P. alni .…”
Section: Methodsmentioning
confidence: 99%
“…However, this tactic has several shortcomings, including a male response bias to the sex pheromone traps and a short duration of residual activity ( Reddy and Guerrero, 2004 ; Said et al, 2005 ). Similar to insect pheromones, plant volatiles are important signaling compounds that regulate insect behavior and exhibit potential as natural pesticides, lures, or antifeedants ( Hanks et al, 2012 ; Hanks and Millar, 2013 ; Jung et al, 2013 ; Collignon et al, 2016 ; Wang F. et al, 2016 ; Wang Y.L. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant volatiles serve as essential cues to insects searching for resources, mates, and oviposition sites (Juma et al, 2016;Hanks et al, 2018;Houjun et al, 2018;Xu and Turlings, 2018). The reception of host-plant volatiles in Lepidoptera is accomplished through a highly sensitive chemosensory system on the antenna, FIGURE 3 | Dosage responses of H. cunea adults EAG to selected host volatile components.…”
Section: Discussionmentioning
confidence: 99%